Demokratisasi Media Massa, Relasi Kuasa Negara Masyarakat dan Pemilik Media (Kajian Terhadap Peran Komisi Penyiaran Indonesia) - jamhur poti (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2016)
Reform that took place in Indonesia in 1998, making a new milestone to the changing circumstances of the authoritarian system towards a democratic system, so that the freedom of speech and expression become more open and guaranteed by law. Apart from that there is also the transfer of power from the management of the regulatory role of the broadcasting system which has been the exclusive rights granted to a state regulatory body that is free (Independent Regulatory Body) namely; The Indonesian Broadcasting Commission to implement the management that broadcasting system which is a public space should be managed by a body that is free from interest intervention powers, certain groups and interests of owners of broadcastmedia itself. KPIs is one of the state institutions in the institutional system of the unitary Republic of Indonesia in accordance to Law No. 32 of 2003. In carrying out its role and powers, KPI has a relationship with other stateagencies to protect the right of people in a more equitable and fair in the field of broadcasting. In the spirit of democratization is the most fundamental changes occurring in the field of broadcasting media, the broadcast media are no longer the guardians of balance (impartially) public space but become part of a mediated between the media, the state and society. In general it can be said that in a democratic system requires the interaction between the state (state), the media (industry), and with society (civil society) were very dynamic, in other words the occurrence of an interaction of the prosperity of society. The relationship between them should be harmonized, in the sense that there is a mutualistic relationship interactive complement and notdominate. However, the question is how the democratization of mass media relations of power of the state, society and media owners as well as the role of KPIs that represent civil society or civil-society, so that the media can carry out their functions freely and independently without being influenced by cooptation capitalist or industry, authorities and no more threats and conflicts will occur. KPI was originally expected to become supervisors and referees who have integrity and no play made in gray with no power against the increasingly powerful media conglomerate cenkramannya invest in the motherland. If the case is not impossible broadcasting media face Indonesia in the future only be an agent of a product of modernity, liberalism andhidonisme.